A influ??ncia da mobiliza????o da ATM sobre os dados estabilom??tricos de indiv??duos com e sem DTM: ensaio cl??nico, controlado, randomizado e simples cego - Amaral, Ana Paula (2012)
This controlled clinical trial, randomized and blinded assessment aims to evaluate the behavior of the COP and mandibular opening in patients with and without TMD after mandibular mobilization nonspecific. The subjects who fitted the inclusion criteria were assessed according to the Research Diagnostic Criteria for Temporomandibular Disorder RDC/TMD (Axis I and II), were divided in two groups, TMD Group and Control Group. Further, the subjects from both groups were assessed using stabilometry which allows the registration of the body oscillations on the antero posterior and medio lateral directions. The assessment was performed in two moments: following a period of10 minutes rest and immediately after the refereed mobilization. Two repetitions were performed for each condition, open and closed eyes, timing seventy seconds. It was possible to verify statistically significant difference on the analyzed variables, when compared pre and post inespecific mandibular mobilization mean values, on TMJ diagnosed subjects, on the open and closed eyes condition. There was statistically significant difference on the center of pressure oscillation area (p<0,03), on the COPml displacement (p<0,006), COPml range (p<0,01) and on the COPap (p<0,03) and COPml (p<0,03) velocity variable, simultaneously. Also, was observed that the mandibular opening movement, of subjects with and without TMD, pre mandibular mobilization is statistically different (p<0,02). According to the comparative analyses of mandibular opening mobility pre and post mobilization, when compared between the TMD and Control Groups was observed statistically significant difference only on the TMD Group (p<0,001). Although, related to the left and right laterality, measured pre and post inespecific mandibular mobilization, was observed statistically significant difference on the increase of range of movement from both groups. These results allow concluding that there is an influence of the inespecific mandibular mobilization on the stabilometric data and on the mandibular range of movement.